Analysis of self-care deficiency among patients with ostomy on the basis of nursing theory of Dorothy Orem - Cierzniakowska, Katarzyna; Kozłowska, Elżbieta; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
Definition of the field of self-care deficiency among patients with ostomy should contribute to elimination of these deficiencies and implementation of direct activities of nursing care which should be made on the highest possible level. Aim: The aim of the study was to define self-care deficiency among patients after procedure ending with ostomy creation. Material and methods: Eighty patients were included in the study. The study was performed in 2005 in the Ostomy Outpatient Clinic of Surgery Clinic from Biziel Hospital in Bydgoszcz, Poland. Studies were anonymous and were performed using a specially constructed questionnaire. Answers were constructed on the basis of a point scale which allowed the assessment of preparation for self-care. It was assumed that 10 points or less indicated unsatisfactory preparation and more than 11 points indicated satisfactory preparation. Results: Collected data indicated that in the study group 12.5% of patients did not manage with self-care. Patient’s education has a significant influence on level of self-care. Conclusions: 1. Proper preparation for self-care is characteristic for patients with secondary and higher education. 2. Training started before surgery significantly decreases self-care deficiency. 3. Early implementation of nursing activities just after the procedure positively influences elimination of self-care problems.